Transformation of the Principle of Sovereignty in a Digital Legal State through Social Media and the Constitution - Inayatulloh, Naflah Naila; Masyami, Masyami; Farhani, Nurilla Alya (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
With the coming of the internet, a new approach has been ushered in which would restate and redefine the concept of sovereignty in states through algorithmic regulation and the mighty transnational digital networks it makes possible. The social media are essentially the decentralized spacesfor legal and political controversy, which tear down the constitutional validity and transform the construction of legitimacy. This study examines how the principle of sovereignty is transformed within a digital legal state by analyzing the interaction between constitutional norms, digital participation, and the growing role of non-state digital actors. A qualitative thematic approach was applied, using data from constitutional documents, court rulings, social media narratives (such as #ReformasiDikorupsi), and semi-structured interviews with legal experts and digital rights advocates. NVivo software program was used to apply thematic coding and categorization. Outcomes are four significant themes: disruption of constitutional sovereignty, digital mediation of sovereignry, coexistence between digital corporations and states, and reinterpretation of constitutional values. Implications are that sovereignty is no longer mapped or geographically located but dynamically negotiated in digital spaces. According to the research, conventional legal models are inadequate and prescribing co-regulatory legal models based on constitutional values is recommended. Citing Indonesia's PDP Law and the EU's Digital Services Act, it emphasizes ASEAN-level collaboration in pushing toward inclusive and accountable digital governance and protecting sovereignty in the post-national setting.